Carrier frequencies of hearing loss variants in newborns of China: A meta‐analysis. Issue 1 (2nd July 2018) - Fu, Yali; Zha, Shuwei; Lü, Nianqing; Xu, Haoqin; Zhang, Xuening; Shi, Wenhui; Zha, Ji
Abstract: Objective: The objective of this study was to review the carrier frequencies of hearing loss gene variants, such as GJB2, SLC26A4, and MT‐RNR1 in newborns of China. Design: PubMed, Embase, BioCentral, CNKI, WanFang, and VIP databases were used for searching relevant literature studies published during the period of January 2007 and January 2016. Meta‐analysis was performed by using the R software. The estimated rate and its 95% confidence intervals (CI) of the relevant indexes in newborns were collected and calculated using a fixed‐effects model or a random‐effects model when appropriate. Results: In total, 35 of 958 published literature studies in Chinese and English were selected. The overall results showed that in newborns of China, the carrier frequencies of GJB2 variants (235 delC, 299 delAT) were 1.64% (95% CI 1.52% to 1.77%) and 0.33% (95% CI 0.19% to 0.51%); SLC26A4 variants (IVS7‐2 A > G, 2168 A > G) were 1.02% (95% CI 0.91% to 1.15%) and 0.14% (95% CI 0.06% to 0.25%); MT‐RNR1 variants (1555 A > G, 1449 C > T) were 0.20% (95% CI 0.17% to 0.23%) and 0.03% (95% CI 0.02% to 0.05%). Conclusions: There are high carrier frequencies of GJB2 variants among newborns in China, followed by SLC26A4 and MT‐RNR1 variants. In order to achieve "early detection, early diagnosis and early treatment" and reduce the incidence of hereditary hearing loss in offspring, a comprehensive combination of neonatal hearing screening and deafness gene detection should be recommended and implemented in China.